2019
DOI: 10.1101/574517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards accurate high-throughput ligand affinity prediction by exploiting structural ensembles, docking metrics and ligand similarity

Abstract: Motivation Nowadays, virtual screening (VS) plays a major role in the process of drug development. Nonetheless, an accurate estimation of binding affinities, which is crucial at all stages, is not trivial and may require target-specific fine-tuning. Furthermore, drug design also requires improved predictions for putative secondary targets among which is Estrogen Receptor alpha (ERα). Results VS based on combinations of Structure-Based VS (SBVS) and Ligand-Based VS (LBVS) is gaining momentum to help character… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This dedicated server called EDMon (Endocrine Disruptor Monitoring; available at: http://edmon.cbs.cnrs.fr/) is now available to screen for ER α , ER β , and peroxisome proliferator–activated receptor- γ (PPAR γ ). It predicts for affinities using a rescoring approach based on machine learning (38). However, the problem is still severe for promiscuous proteins, such as the nuclear receptors CAR (constitutive androstane receptor) and PXR (pregnane X receptor) (39).…”
Section: Structure-based Methodsmentioning
confidence: 99%
“…This dedicated server called EDMon (Endocrine Disruptor Monitoring; available at: http://edmon.cbs.cnrs.fr/) is now available to screen for ER α , ER β , and peroxisome proliferator–activated receptor- γ (PPAR γ ). It predicts for affinities using a rescoring approach based on machine learning (38). However, the problem is still severe for promiscuous proteins, such as the nuclear receptors CAR (constitutive androstane receptor) and PXR (pregnane X receptor) (39).…”
Section: Structure-based Methodsmentioning
confidence: 99%
“…Nevertheless, the in silico study results indicated that the binding scores did not show a good correlation with the in vitro experiment obtained. The comparative study found that the binding affinity's predictive power is relatively low than a structurebased feature [32] . Fig.…”
Section: Abstract: Lipoxygenase Xanthine Oxidase Inhibition Aminomethyl Dehydrozingeronementioning
confidence: 96%
“…Many zinc proteins are established, or potential, drug targets (Anzellotti and Farrell, 2008;Krezel and Maret, 2016;Parkin, 2004). While progresses were made in molecular docking algorithms (Ballester and Mitchell, 2010;Boyles, et al, 2020;Cang and Wei, 2017;Johansson-Akhe, et al, 2020;Lu, et al, 2019;Schneider, et al, 2020;Velazquez-Libera, et al, 2020;Wang, et al, 2019;Zhang and Sanner, 2019) according to recent assessment (Li, et al, 2014;Su, et al, 2019), metalloproteins were found more challenging than nonmetalloproteins for docking because of additional interactions involving with metal ions. Hu et al (Hu, et al, 2004) showed that a correct zinc-coordination geometry is essential for the state-of-the-art docking software FlexX, Autodock, and GOLD (Jones, et al, 1995;Jones, et al, 1997;Kramer, et al, 1999;Morris, et al, 2009;Rarey, et al, 1996;Trott and Olson, 2010) to achieve a reasonable prediction.…”
Section: Introductionmentioning
confidence: 99%